Collaborative Teaching in Inclusive Kindergarten Education: A Qualitative Study of Spontaneous and Structured Partnership Models - Suwarlis, Suwarlis; Hermanto, Hermanto; Pujaningsih , Pujaningsih (Journal of Innovation and Research in Primary Education, 2025)
This study examined teacher collaboration patterns in inclusive kindergarten education to understand how classroom teachers and special education support teachers coordinate their efforts in supporting children with special needs. Using qualitative case study methodology, data were collected through structured observations, semi-structured interviews, and document analysis at two kindergarten institutions in East Kutai Regency, Indonesia. Participants included principals, classroom teachers, special education support teachers, and children with special needs from both institutions. The study revealed two distinct collaboration models: spontaneous collaboration characterized by immediate problem-solving and flexible role adaptation, and structured collaboration emphasizing systematic planning and preparation. Both approaches demonstrated effectiveness through complementary expertise integration, shared accountability, and trust-based relationships. Key challenges included communication inconsistencies, limited specialized resources, and informal documentation processes. However, collaborative practices resulted in enhanced student inclusion, professional growth through mutual learning, and improved educational outcomes for children with special needs. The findings contribute to theoretical understanding of collaborative teaching by demonstrating that effective partnerships can emerge through multiple pathways while maintaining shared commitment to inclusive education principles. The research provides evidence-based recommendations for teacher preparation programs, professional development initiatives, and institutional support structures in early childhood inclusive education settings.